Optimization of integrated watershed recovery: comparison of management systems in Japan and Indonesia - Kristi Siagian; Iwan Freddy Sidabutar; Raldi Hendro Koestoer (Institute for Advanced Science Social, and Sustainable Future, 2023)
As a country prone to hydrometeorological disaster and demographic problems, Japan is very concerned about integrated watershed sustainability, as a preventive and sustainable water resource in the future. In contrast to Indonesia, the rapid population growth encourages various activities in the upstream such as encroachment, conversion to agricultural land, settlements, and other economic activities causing land degradation and environmental quality to decline. The critical watershed recovery program has been carried out for a long time, but until now this problem has not been resolved. This study aims to determine the best integrated watershed management system that can be applied to accelerate the recovery of critical watersheds in Indonesia. This study uses a qualitative approach, with a comparative descriptive method to compare watershed management in Japan and Indonesia based on a literature study. It was found that land rehabilitation activities through replanting upstream watershed areas require collaboration in comprehensive and integrated management from upstream to downstream. The practice of inter-regional cooperation and community involvement through cross-subsidized funding and joint restoration activities is a scheme that needs to be considered for accelerating watershed recovery, accompanied by the integrity of the parties and a transparent and accountable monitoring system.